2012
DOI: 10.1007/s40145-012-0018-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube formation using zeolite template and applications

Abstract: Carbon nanotubes (CNTs) have attracted intensive interests of researchers for a long time due to their fascinating physical and chemical properties promising for various potential applications, including advanced ceramics, nanoelectronic devices, nanoscale sensors, solar cells, battery electrode, field emitters, etc.. This review summarized the synthetic methods of CNTs, with an emphasis on the chemical vapor deposition (CVD) method, especially catalytic CVD. Although there still are some challenges in the way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…storage materials and electrocatalysts: more specifically, high specific surface area is beneficial for gas adsorption [73] and improvement of double layer capacitance; [55,[74][75][76][77][78][79] the zeolite-templated carbon frameworks with high conductivity are also suitable candidates as electrode materials [55,73,74,77,[79][80][81][82][83][84][85][86][87][88][89][90] and promising scaffolds for electrocatalysts; [81,[91][92][93][94][95][96] hierarchically ordered porosity can enhance mass transfer without pore blockage, [78,91,[97][98][99] which has already been employed as the host of active materials in electrode; [83,85,100] plus ultrafine nanostructures anchored on zeolite-templated nanocarbons, enhanced electrocatalytic performance can be implemented by synergic effect of nanocarbons and metal nanostructures. [81,91] The definition of nanocarbons was proposed by Inagaki et al, [101,102] which contemplates not only the control of size but also the control of struct...…”
Section: Introductionmentioning
confidence: 99%
“…storage materials and electrocatalysts: more specifically, high specific surface area is beneficial for gas adsorption [73] and improvement of double layer capacitance; [55,[74][75][76][77][78][79] the zeolite-templated carbon frameworks with high conductivity are also suitable candidates as electrode materials [55,73,74,77,[79][80][81][82][83][84][85][86][87][88][89][90] and promising scaffolds for electrocatalysts; [81,[91][92][93][94][95][96] hierarchically ordered porosity can enhance mass transfer without pore blockage, [78,91,[97][98][99] which has already been employed as the host of active materials in electrode; [83,85,100] plus ultrafine nanostructures anchored on zeolite-templated nanocarbons, enhanced electrocatalytic performance can be implemented by synergic effect of nanocarbons and metal nanostructures. [81,91] The definition of nanocarbons was proposed by Inagaki et al, [101,102] which contemplates not only the control of size but also the control of struct...…”
Section: Introductionmentioning
confidence: 99%
“…Well-aligned CNTs have also been synthesized on glass template from acetylene gas by plasma-enhanced CVD process [26]. Zeolites have also been employed as controlling agents during CNTs growth [27].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been reported in open literature for incorporation of liquid and solid lubrication in ceramics, particularly for Si 3 N 4 and its composites with a goal to reduce friction and wear [7][8][9][10][11]. However, liquid lubricants on ceramic surfaces are less efficient, due to their poor reactivity with ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Tribological studies on nanoparticles have proved that lubricants with different nanoparticles as additives are effective in reducing friction and wear for metallic tribo pairs, whereas limited work has been reported in ceramics. A number of researchers have reported that the addition of nanoparticles, such as copper oxide, molybdenum disulphide, etc., to the conventional lubricants are effective in reducing friction and wear in both metallic and ceramic tribo pairs [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Nanodiamond additives to mineral oil have already proved effective in friction and wear reduction in various engineering applications, under higher load and low velocity conditions.…”
Section: Introductionmentioning
confidence: 99%